Effectiveness of Complex Agility Training Program for Amateur Male Soccer Players - Thongnum, Pattarapol; Phanpheng, Yanyong Yanyong (Physical Education Theory and Methodology, 2022)
Background. The ability to quickly change direction has been considered an important physical quality related to success in youth soccer. The study purpose was to investigate the training effect of a complex agility training program on amateur male soccer players. Materials and methods. The participants were 60 amateur male football players (aged 18-22) divided into two groups and selected by using purposive random sampling. Thirty athletes aged 19.7±1.34, BMI 21.8±1.75 performed a complex training program (CTG) combined with sprint, agility or CoD, and plyometric session. While 30 participants of the control group (CG) aged 19.3 ± 1.31, BMI of 21.2 ± 1.02 followed a general football training program. In both groups, each training session lasted 120 minutes, a 30-minute period, 3 times a week, a total of 6 weeks. The Arrowhead Agility Test was scheduled at the baseline, for the 4th and 6th weeks. The mean and standard deviation of the data was calculated. The inferential statistic was repeated measure ANOVA. A Newman-Keuls post hoc test was calculated if the group x time interactions were significant (p < 0.05). Results. After training, agility was a statistical difference within the CTG, when comparing baseline and the 6th week (p = 0.03), there were no significant changes in agility when comparing between-group. Therefore, this shows that complex training programs can improve agility in amateur male soccer players. Conclusions. This integrated training program can be applied to amateur male soccer players. The training program should be specific and varied. It can help soccer players improve their agility that is related to overall soccer performance.